Substitusi Silang Anggaran: Pola Mekanisme Penganggaran Pada Organisasi Intrakampus - Rohma, Frida Fanani (AKTIVA: Journal Of Accountancy and Management, 2023)
Purpose: This study aims to investigate budgeting practices in intracampus organizations. Budgeting is a key activity that has the potential to cause dysfunctional behavior and irregularities in the organization. The development of the literature shows that fraud that occurs at the higher education level is one of the predictors of fraud that occurs in a country. Thus, it is necessary to explore budgeting patterns in intracampus organizations.Design/methodology/approach: This study employs a qualitative method with a case study approach that sees an intra-campus organization as a research site.Research Findings: There is a tendency for organizations to increase work program variances rather than work program proposals. The large variance of work programs makes organizations tend to make cross-budget substitutions to realize the entire work program. The large variance of work programs implemented with a cross-budget substitution mechanism has the potential to cause work program achievements to be sub-optimal.Contribution/Originality/Novelty: Previous research only focus in budgeting. This study complements previous studies by considering the practice of budgetary slack in intracampus organizations. Research provides new insights that cross-substitution efforts have the potential to reduce performance effectiveness. Tujuan Penelitian: Penelitian ini bertujuan untuk menginvestigasi praktik penganggaran pada organisasi intrakampus. Penganggaran merupakan aktivitas kunci yang berpotensi menyebabkan terjadinya perilaku disfungsional dan penyimpangan pada organisasi. Perkembangan literatur menunjukkan bahwa kecurangan yang terjadi pada level Pendidikan tinggi menjadi salah satu prediktor kecurangan yang terjadi disuatu negara. Dengan demikian, diperlukan upaya eksplorasi pola penganggaran pada organisasi intrakampus.Desain / metodologi / pendekatan: Penelitian ini menggunakan metode kualitatif dengan pendekatan studi kasus yang melihatkan salah satu organisasi intra kampus sebagai situs penelitian.Temuan Penelitian: Terdapat kecenderung organisasi memperbanyak varians program kerja daripada usulan program kerja. Besarnya varians program kerja membuat organisasi cenderung melakukan substitusi silang anggaran untuk merealisasikan keseluruhan program kerja. Besarnya varians program kerja yang terlaksana dengan mekanisme substitusi silang anggaran berpotensi menyebabkan capaian program kerja menjadi tidak optimal.Kontribusi / Orisinalitas / Kebaruan: Penelitian ini melengkapi kajian sebelumnya dengan mempertimbangkan praktik kesenjangan anggaran pada organisasi intrakampus. Penelitian memberikan wawasan baru bahwa upaya substitusi silang berpotensi menurunkan efektivitas kinerja.